Marine Cyanophyceae of Papua New Guinea. III. The Genera Borzia and Oscillatoria - Hoffmann, L.; Demoulin, V. (Botanica Marina, 1993)
In the framework of a survey of the marine Cyanophyceae of Papua New Guinea, material was collected along the north coast (Madang Province) and the south coast (Central Province). Thirteen taxa belonging to the genera Borzia (2 taxa) and Oscillatoria (11 taxa) were recorded, especially in the infralittoral zone. All of them are new records for Papua New Guinea; nine of them, i. e. Borzia papuana, Oscillatoria bonnemaisonii var. minor, O. boryana var. marina, O. castanea, O. laetevirens var. papuana, O. laingii, O. olivaceobrunnea, O. olivaceobrunnea var. motuporensis, O. subuliformis var. major are new for science. The two Borzia species are endozoic, whereas the Oscillatoria taxa are epipsammic or epiphytic.